Transition milestones and life satisfaction at ages 25/26 among cohorts born in 1970 and 1989–90. (March 2022) - Gagné, T.; Sacker, A.; Schoon, I.
Abstract: The transition to adulthood has become more prolonged, complex, and risk-laden over the past two decades. These changes may contribute to the decline in wellbeing observed among young adults. We test the role of reaching different transition milestones on life satisfaction by ages 25–26 among men and women born 20 years apart in 1970 and 1989–90, using data from the 1970 British Cohort (men n  = 3764, women n = 4568) and Next Steps (men n  = 3246, women n  = 4281) studies. We regressed life satisfaction on education, housing tenure, cohabitation with parents, economic activity, relationship status, and parenthood, and tested the role of changes in the prevalence and association of milestones in explaining cohort differences in life satisfaction using decomposition analyses. Home ownership, full-time employment, cohabitation with a partner, and marriage were robust predictors of life satisfaction in both cohorts. Comparing cohorts, the association of milestones with life satisfaction was stable among men but differed among women: in the later-born cohort, women no longer benefitted from higher education and further suffered from not being in full-time employment. The findings shed new light on the relationships between young adult transitions and life satisfaction during the third decade of life. These support the argument that decreases in wellbeing may be driven by changes in the prevalence and meaning of these milestones over time, particularly among women. Highlights: Life satisfaction (LS) at ages 25–26 decreased between those born in 1970 and 1989–90. Employment, independent living, and partnership were associated with higher LS in each cohort. Education was no longer positively associated with LS among women in the later-born cohort. Employment and independent living were more strongly associated with LS in women in the later-born cohort. Changes in LS at ages 25–26 are likely to be attributable to changes in transition milestones.